2020
DOI: 10.1002/aenm.201903181
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Single Atom Electrocatalysis, Where “Singles” Are “Married”

Abstract: There is an intensive search for heterogeneous single atom catalysts (SACs) of high activity, efficiency, durability, and selectivity for a wide variety of electrocatalytic conversion and chemical reactions, such as the hydrogen evolution reaction (HER), oxygen evolution/reduction reaction (OER and ORR), CO2 reduction reaction (CO2 RR), and nitrogen reduction reaction (NRR). With the downsizing from nanoparticles and clusters to single atoms, there are steady changes in the bond and coordination environment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 132 publications
(180 reference statements)
2
105
0
Order By: Relevance
“…efficient HER. [12][13][14] However, to the best of our knowledge, successful HER application of SACs in alkaline seawater has not been properly realized yet. In addition, the intrinsic HER mechanism of SACs involves rather complicated pathways occurring at the atomically dispersed metal species.…”
mentioning
confidence: 99%
“…efficient HER. [12][13][14] However, to the best of our knowledge, successful HER application of SACs in alkaline seawater has not been properly realized yet. In addition, the intrinsic HER mechanism of SACs involves rather complicated pathways occurring at the atomically dispersed metal species.…”
mentioning
confidence: 99%
“…In addition, the synergistic effect between single atom sites and atomic clusters is very effective in breaking the limitation of the proportional relationship between electrocatalysis and other types of multi‐step reactions. [ 101‐103 ] In this category of electrocatalyst, a single atom can act as an active catalytic site, and nanoclusters can increase the conductive channels of charge flow in time of an electrochemical reaction.…”
Section: Structure–property Effects For Atomic Level Dispersed Metal–mentioning
confidence: 99%
“…Recently, single-atom electrocatalysts (SACs), which comprise singly isolated metal atoms immobilized onto a heterogeneous support, have attracted intensive attention as a robust analogue of organometallics. [17][18][19][20][21][22][23][24] SACs are the ultimate form of size reduction of metal electrodes, and they maximize the efficiency of metal atom use. Furthermore, some SACs exhibit unique electrocatalytic activity and selectivity.…”
Section: Kazuhide Kamiya Received Hismentioning
confidence: 99%
“…SACs with dened coordination structures on inorganic supports, including nanocarbons, metal oxides, and nitrides, have recently been developed and are well summarized in reviews. 23,24 For example, Kou and Wang et al synthesized single Mo sites with an Mo 1 N 1 C 2 local coordination structure in nitrogen-doped carbons and used them as efficient bifunctional OER/ORR and nitrogen reduction reaction catalysts. 25,26 The same authors nicely demonstrated that the single Co atoms which are coordinated with three Mo atoms in the 2D molybdenum carbide nanosheets served as effective active sites for both the OER and the HER.…”
Section: Kazuhide Kamiya Received Hismentioning
confidence: 99%